PSIV-32 Effects of Viligen™ on growth performance of 6 to 13 kg nursery pigs. (7th December 2018) - Fruge, E; Gerhart, A; Hansen, E; Hansen, S; Frerichs, K
Abstract: Two experiments were conducted in a commercial research facility to determine the effects of a proprietary blend of short chain fatty acids and prebiotic components (Viligen™; Alltech Inc., Nicholasville, KY) on nursery pig performance. Experiments were arranged in a randomized complete block design with 6 replications per treatment and 28 pigs per pen. Pigs were randomly allotted to one of two dietary treatments which consisted of a control diet (CON) or the control diet with 0.135% Viligen™ (VIL) fed in two phases of pelleted diets without antibiotics and with 2000 ppm dietary zinc. In Exp. 1 and 2, 336 mixed-sex pigs (TN Tempo x TN70), 6.33 ± 0.26 kg BW, 5.92 ± 0.35 kg BW, were used in each 22 and 24-d Exp., respectively. Pen weights and feed disappearance were recorded on d0, d11, d22 or d24 and used to calculate ADG, ADFI, and GF. Growth data were analyzed using the GLM procedures of SAS (Cary, NC). Only cumulative growth data for both experiments are presented (Table 1). Pigs fed VIL had improved (P < 0.01) ADG, ADFI, and BW gain compared to pigs fed the CON diet. A treatment by Exp. interaction was observed (P < 0.01) for GF where pigs fed VIL had improved GF (0.86 vs. 0.91) in Exp.1 but similar GF (0.85 vs. 0.85) in Exp. 2. A reduction in injectable medication use (P < 0.03) was noted in pigs fed VIL. Furthermore, a numerical improvement (P > 0.10) in mortality and morbidity was observed for pigs fed diets containing VIL. Together these studies suggest improvements in performance and overall health that can result in more pigs reaching the finisher stage of production.